Digitally programmable organic light‐emitting tetrodes. Issue 2 (2nd November 2022) - Ji, Junpeng; Yang, Biao; Zhang, Chaohong; Cai, Yulu; Chen, Jingwei; Zhao, Changbin; Wang, Tao; Wu, Lijie; Liu, Ming; Bai, Junwu; Wang, Jiangfeng; Wu, Zhongbin; et al.
Abstract: Limited to the structure of traditional light‐emitting devices, electronic devices that can directly convert machine language into human visual information without introducing any back‐end circuit are still not easy to achieve. Based on a specially designed three‐phase co‐planar electrode structure, a new type of three‐phase alternating current driven organic light‐emitting device with the integration of emission and control functions, full‐color tunability and simple device structure is demonstrated in this study. We integrate the light‐emitting function of color‐tunable light‐emitting devices and the switching of three triodes in a single three phase organic light‐emitting device. The state control of luminous color and luminance intensity merely requires the introduction of a kind of machine language, that is an easy‐to‐program 6‐bit binary number coded digital signals. The color adjustable area covers 66% of the color triangle of the National Television System Committee. Such simple and easy‐to‐integrate light‐emitting system has great potential applications in the next‐generation man‐machine interface. Abstract : A new concept of electronic device that directly converts codeable digital signals into visible information is reported. This new type of device containing three light‐emitting units needs only one digital signal to integrate and control the light‐emitting state of the entire pixel, which is expected to reduce 2/3 of the switching devices.